Razvojne spremembe v intelektualnem delovanju pri osebah z motnjo v duševnem razvoju - Žerak, Urška (Psihološka obzorja (Ljubljana), 2018)
The aim of the study was a retrospective, longitudinal investigation of changes in intellectual functioning in individuals with intellectual disability who were/are institutionalised. Development of individuals with intellectual disability differs from the development of individuals with typical development, as these individuals frequently demonstrate regressions and fluctuations in development. Their development depends on the type and extent of the intellectual disability, comorbid psychopathology and health conditions. The sample included 30 individuals with moderate (21) and severe (9) intellectual disability who had been assessed in three different time points with an instrument measuring intellectual ability (Valentine intelligence test for children). The group analysis showed a statistically significant improvement in the scores on measured construct between first and second point and continuity of achievements during the second and third point. Results indicate congruity with the similar-trajectory hypothesis, which predicts growth of intellectual abilities up to 20 years, then continuity and decline around age 60. Limitations and guidelines for future research are also discussed.
Keywords: cognitive development; early adulthood; intelektualni razvoj; inteligentnost; intellectual development; intellectual disability; intelligence; Intelligence test for children; late childhood; mental handicap; middle childhood; motnje v duševnem razvoju; pozno otroštvo; spoznavni razvoj; srednje otroštvo; Valentine test inteligentnosti; vzdolžne študije; zgodnja odraslost